2016
DOI: 10.14745/ccdr.v42i12a06
|View full text |Cite
|
Sign up to set email alerts
|

Invasive serogroup W Neisseria meningitidis (MenW) in Ontario, Canada shows potential clonal replacement during the period January 1, 2009 – June 30, 2016

Abstract: Background: In Ontario, serogroup W Neisseria meningitidis (MenW) accounts for a small percentage of all invasive meningococcal disease (IMD) and between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…From 2000 to 2013, the majority of MenW diseases were caused by strains belonging to the ST-22 CC. Beginning in 2014, a significant shift in the genetic makeup of invasive MenW strains was noted, from ST-22 CC to ST-11 CC (Tsang et al, 2016). Concomitant to this genetic shift in the MenW strain was the increase in the proportion of IMD due to MenW (Tsang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From 2000 to 2013, the majority of MenW diseases were caused by strains belonging to the ST-22 CC. Beginning in 2014, a significant shift in the genetic makeup of invasive MenW strains was noted, from ST-22 CC to ST-11 CC (Tsang et al, 2016). Concomitant to this genetic shift in the MenW strain was the increase in the proportion of IMD due to MenW (Tsang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…MenW ST-11 disease in university students has also been reported from France (Bassi et al, 2017). While no fatal MenW ST-11 cases were identified in one Canadian study (Tsang et al, 2016), both the UK and Australia have reported high case-fatality rates (of 12% and 10.7%, respectively) (Efron et al, 2009;Campbell et al, 2016). Unusual clinical presentations of predominantly gastrointestinal symptoms, but also necrotizing fasciitis, have also been reported from Europe (Campbell et al, 2016;Russcher et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The South American strain sublineage includes three strains: the South American strain, the original UK strain (a descendent of the South American strain that emerged in 2009 in the United Kingdom), and a further descendent strain, called the UK 2013 strain [17]. These hypervirulent strains belonging to the South American MenWcc11 sublineage are responsible for the rise in MenW incidence observed in Brazil, Argentina, Chile, the United Kingdom, the Netherlands, Spain, and other European countries, Canada, and Australia [17][18][19]. Interestingly, unusual clinical presentations including gastrointestinal symptoms, high morbidity, and increased case fatality rates have been described in several countries associated with IMD because of the South American MenWcc11 sublineage [12,20].…”
Section: Introductionmentioning
confidence: 99%